(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The Nepal-India relationship has historical, social, political, and cultural facets that are multidimensional. Open borders and deeply rooted people to-people contacts of kinship and culture distinguish the unique friendship and cooperation between the two nations. Based on secondary data, the purpose of this article is to discuss the major changes in Indo-Nepal relations following an understanding of 12 points. EPG was established with four members from each of Nepal’s and India’s governments in order to examine previous agreements and treaties. In a similar vein, India and Nepal exchanged high-level visits. In 2015, Nepal adopted a new constitution and published it. However, India unilaterally imposed a blockade because it was dissatisfied with some of its contents. Later, relations between Nepal and India normalized, but Nepal and India still disagree about the Limpiyadhura-Lipulekh border. What has become of the relationships based on past ties? This is the most pressing issue. This paper examines the past and present of India’s relations with Nepal.